Engineering-Oriented Transit QoS and Perceived Value: Predicting Passenger Satisfaction and Behavioral Intentions in Urban Public Transport - Muhamad Fajar Subkhan; Endang Siti Astuti; Andriani Kusumawati; Sunarti Sunarti (International Journal of Environment, Engineering and Education, 2026)
The integration of technology into education has garnered significant interest, particularly for its potential to support environmental sustainability. Urban bus and bus rapid transit (BRT) systems must deliver passenger-centered service quality that is both measurable for operators and meaningful to users. However, service-quality research often relies on generic perceptual scales that are difficult to translate into actionable operational interventions. This study advances an engineering-oriented Stimulus–Organism–Response (S–O–R) framework by conceptualizing Transit Engineering Quality of Service (TE-QoS) as an actionable stimulus and examining its relationships with perceived value, satisfaction, and behavioral intention in the context of urban bus services in Indonesia. Data were collected through an offline intercept survey of Trans Jatim passengers in the Surabaya metropolitan area between June and July 2024, yielding 300 valid responses for analysis. Using CB-SEM (AMOS), the measurement model demonstrated satisfactory reliability and validity. The structural results indicate that perceived value strongly predicts satisfaction (β = 0.698, p < 0.001), whereas TE-QoS exerts a positive, though comparatively modest, direct effect on satisfaction (β = 0.122, p = 0.017). Satisfaction, in turn, strongly predicts behavioral intention (β = 0.700, p < 0.001). The Model explains 50.2% of the variance in satisfaction and 48.9% of the variance in behavioral intention. These findings suggest that operational improvements in reliability, regularity, travel-time efficiency, access, comfort, information, and safety are more likely to strengthen loyalty-related intentions when passengers perceive them as clear gains in value. Future research should integrate objective operational data and formally examine indirect mediation pathways.